IIR notch filter design with modified pole-zero placement algorithm - Yimman, S.; Hinjit, W.; Sriboonsong, S.; Puangpool, M.; Dejhan, K. (My University, 2003)
The following paper presents the design and implementation of IIR notch filter with modified pole-zero placement algorithm. The proposed modified algorithm is derived from the least square estimation to change the pole position and find the estimated values of coefficients to control the new gain level of the pass-band. The results from the algorithm are shown, the algorithm could control the pass-band gain of the notch filter according to the specifications. The result has been simulated by using MATLAB.
Keywords: Algorithm design and analysis; Approximation algorithms; Band pass filters; Bandwidth; Biomedical engineering; Cutoff frequency; Finite impulse response filter; IIR filters; Least squares approximation; Poles and zeros